2016
DOI: 10.1111/risa.12537
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Risk Perceptions, and Xenophobic Attitudes: Evidence from Italy During the Ebola Outbreak

Abstract: The purposes of the current study were twofold: (1) to investigate affective and cognitive responses and social-contextual factors related to Ebola and their intercorrelations in a developed country without widespread Ebola transmission; and (2) to examine the relationships among risk perception of Ebola, levels of knowledge about Ebola, and (blatant and subtle) prejudice toward African immigrants. Between January 2015 and March 2015, an anonymous cross-sectional survey was conducted among a convenience sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 30 publications
6
62
0
2
Order By: Relevance
“…Although we must extrapolate cautiously to other times in the United States or other settings in the world, other studies have also reported seemingly measured responses, despite expert and pundit concerns about “panic.” For example, a U.S. survey conducted near the height of public concern (October 21–November 4, 2014) found that, despite being highly salient, Ebola was viewed only as a moderate risk and evoked only moderately high emotions, with sadness being the strongest . A survey conducted in Italy in early 2015 found even lower concern . Related results have been reported from Germany and Israel, among other places .…”
Section: Discussionmentioning
confidence: 85%
“…Although we must extrapolate cautiously to other times in the United States or other settings in the world, other studies have also reported seemingly measured responses, despite expert and pundit concerns about “panic.” For example, a U.S. survey conducted near the height of public concern (October 21–November 4, 2014) found that, despite being highly salient, Ebola was viewed only as a moderate risk and evoked only moderately high emotions, with sadness being the strongest . A survey conducted in Italy in early 2015 found even lower concern . Related results have been reported from Germany and Israel, among other places .…”
Section: Discussionmentioning
confidence: 85%
“… 47 48 Similarly, Ebola-related stigma and xenophobic attitudes have been reported elsewhere outside of directly affected countries. 26 49 50 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also measured Ebola-related KAP within different populations in sub-Saharan Africa 15–25 and other parts of the world. 26–30 However, few national-level KAP studies have been conducted in Ebola affected countries during periods of active transmission. The present study represents the first national Ebola KAP survey in Sierra Leone—conducted in August 2014—within the first 3 months of a prolonged epidemic that lasted over a year.…”
Section: Introductionmentioning
confidence: 99%
“…Conversations with others, even those not in danger or suspected to be in danger, can also amplify or attenuate the emotional response to an attack . The perception of risk is also constructed and made sense of via conversation within social communities about what is risky and worth worrying about . Conversation within personal networks can thus lead individuals in one social group to dread an outcome that is accepted as normal in another .…”
Section: Introductionmentioning
confidence: 99%